Aplikabilitas Kepemimpinan Paternalistik di Indonesia - Irawanto M.Com. PG.Cert.HRM, Dodi Wirawan (Journal of Human Capital, 2008)
Organisational leadership play a vital role on the organizational effectiveness. A number of leadership theories thatreflectto Western model may inappropriate to Indonesian culture. Paternalistic leadership is a leadership model that originates from Eastern culture (Taiwan). Looking at the culture similarities between Taiwan and Indonesia culture, itis predicted that paternalistic leadership will workeffectively in Indonesian context. A combination of benevolent leadership, moral leadership and authoritarianism leadership may be applicable to Indonesian culture in which emphasizing high degree of social harmony. This study done at East lava province on 50 respondents and can be concluded that paternalistic leadership concept is applicable to Indonesians' and having moral leadership as a preferable leadership style by subordinates. Key words : Paternalistic, Leadership, Benevolent. Moral, Authoritarianism, Culture, Organization